Population Genetics of Tor douronensis in Sarawak – A Revisit - Muhammad Amirul Arib, Md Adzhar; Ruhana, Hassan (Universiti Malaysia Sarawak (UNIMAS), 2015)
Tor douronensis, known locally as Semah, is one of the valuable resources of Sarawak due to its high nutritional value and demand as game fish. Several molecular studies related to T. douronensis have been carried out and deposited in GenBank including the data collected from Ba Kelalan, Layar and Limbang. Although there are other studies on Tor spp., the data was not available in GenBank, thus there are not included in the analysis. One fieldtrip to Bakun Dam was carried out on June 2014 with initial aim to assess overall fish diversity. During this sampling, 11 individuals of T. douronensis were caught, which later subjected to molecular work to investigate the genetic structure and evolutionary relationship among four of T. douronensis in Sarawak using partial Cytochrome c oxidase I (COI) mtDNA gene. A fragment of 465 bp of CO1 gene of T. douronensis was successfully amplified. Based on the phylogenetic trees generated, three clades could be observed namely Central, Southern, and Northern populations; 1st clade (haplogroup I) from Bakun, 2nd clade (haplogroup II) from Layar and 3rd clade (haplogroup III) from Ba Kelalan and Ulu Limbang. Overall, there were 13 haplotypes and none was shared among populations, suggesting low level of inter-population gene flow has been observed. The small number of migrants per generation (Nm<1.0) among the population indicated that the small populations were isolated possibly due to large geographical areas. All population had undergone expansion with a large negative value and significant test of Fu’s F in Bakun population suggested recent expansion. In addition, result also suggested that all populations did not deviate from evolutionary neutrality.